2018
DOI: 10.22627/2072-8107-2018-17-3-57-61
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Exanthema in Children

Abstract: The article considers the main childhood infections that occur with the exanthema. Rules for the description of exanthemа, their classification, basic differential-diagnostic symptoms are presented. The article is illustrated with photographs of their author's archive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In general blood analysis of patients with uncomplicated measles Pokrovska et al (2015) revealed leukopenia with relative lymphocytosis in only 20.9% of adults and 25.7% of children, with no children under one year having leukopenia in any case, most often the normal number of leukocytes with stab neutrophil shifting of leukocyte formula to the left (63.4%). Leukopenia or normocytosis is also reported by Utenkova (2018). Every fifth child with measles showed leukopenia within 4-6 days of the disease onset according to Kramarov et al (2018), Yevtushenko et al (2019).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In general blood analysis of patients with uncomplicated measles Pokrovska et al (2015) revealed leukopenia with relative lymphocytosis in only 20.9% of adults and 25.7% of children, with no children under one year having leukopenia in any case, most often the normal number of leukocytes with stab neutrophil shifting of leukocyte formula to the left (63.4%). Leukopenia or normocytosis is also reported by Utenkova (2018). Every fifth child with measles showed leukopenia within 4-6 days of the disease onset according to Kramarov et al (2018), Yevtushenko et al (2019).…”
Section: Discussionmentioning
confidence: 92%
“…The rules for serological examination of patients with suspected measles were observed (Utenkova, 2018). The blood serum was selected on days 4-5 from the rash onset, and not later than day 28 from the moment of the rash onset.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations